Expert system for scheduling and control of highway construction projects - Bentotage, Sunil Nandalal; Ogunlana, Stephen O.; Arditi, David; Maekawa, Koichi; King's Scholarship; The Royal Thai Government (Bangkok : Asian Institute of Technology, 1992)
Activities involved in highway construction, their precedence relations and the activity durations are highly dependent on site, environmental and management conditions. Depending on those conditions, the number of options available to perform the same activity under different situations is found to be very high. Computerized support on the generation of construction schedules is currently limited to the provision of network for manually defined and sequenced activities. With the development of the expert system technology, it has been possible to develop a knowledge based expert system, ROAD PLANNER to deal with such situations. Knowledge ac quisition, formulation of the elicited knowledge and building of both data bases and rule bases are the three major phases involved in the. system development. Eleven main activities to be present in the majority of highway projects, have been defined at its root level of the system. According to the user information on the existence of above main activities, the system generates the precedence relationships. Consequently, several rule bases and data bases interact to generate sub activities and activity durations by extracting necessary information from the user. Prece dence network technique has been considered to express the relation among activities as most highway construction activities are found to be parallel. Concept on the 'required completion before the commencement of successor' has been extended towards the consequent derivation of lead and lag times.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1992
Keywords: Scheduling (Management); Road construction industry -- Management; Expert systems (Computer science)